Public Administration training policy and enhancing capacity of Bangladesh civil service: a review - Hasan, Md. Mahmudul (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2009.